1974
DOI: 10.1143/jjap.13.203
|View full text |Cite
|
Sign up to set email alerts
|

Undopedn-Type GaSb Grown by Liquid Phase Epitaxy

Abstract: In this paper we investigate the effect of stochasticity in the spatial and temporal distribution of supernova remnants on the spectrum and chemical composition of cosmic rays observed at Earth. The calculations are carried out for different choices of the diffusion coefficient D(E) experienced by cosmic rays during propagation in the Galaxy. In particular, at high energies we assume that D(E) ∝ E δ , with δ = 1/3 and δ = 0.6 being the reference scenarios. The large scale distribution of supernova remnants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…88,92,93 Capasso and co-workers 88 could achieve very low net donor concentration in the range of 10 14 -10 15 cm Ϫ3 from undoped Ga-rich solutions in the 300-375°C range and by Te compensation using Ga-rich melt at 500°C. Miki and co-workers 94 were also able to grow undoped n-type layers at 400°C from Ga-rich melt with net donor concentration of ϳ10 15 cm Ϫ3 and mobility as high as 7700 cm 2 /V s. In our studies we have observed that undoped layers grown from antimony-rich melts always exhibit p-type conductivity irrespective of the growth temperature. 96 In contrast, a type conversion from p to n was observed in layers grown from Ga-rich melts below 400°C.…”
Section: Liquid Phase Epitaxysupporting
confidence: 65%
See 1 more Smart Citation
“…88,92,93 Capasso and co-workers 88 could achieve very low net donor concentration in the range of 10 14 -10 15 cm Ϫ3 from undoped Ga-rich solutions in the 300-375°C range and by Te compensation using Ga-rich melt at 500°C. Miki and co-workers 94 were also able to grow undoped n-type layers at 400°C from Ga-rich melt with net donor concentration of ϳ10 15 cm Ϫ3 and mobility as high as 7700 cm 2 /V s. In our studies we have observed that undoped layers grown from antimony-rich melts always exhibit p-type conductivity irrespective of the growth temperature. 96 In contrast, a type conversion from p to n was observed in layers grown from Ga-rich melts below 400°C.…”
Section: Liquid Phase Epitaxysupporting
confidence: 65%
“…There exist quite a few reports on growth of GaSb by LPE technique. [87][88][89][90][91][92][93][94][95][96] Ga-, Sb-, Sn-and Bi-rich melts have been used for the growth in the temperature range of 330-680°C. By carrying out growth at low temperatures, the native acceptor concentration could be reduced to a level of 10 16 cm Ϫ3 .…”
Section: Liquid Phase Epitaxymentioning
confidence: 99%
“…15 ρ ϭ * ρ ϭ * µ ϭ * µ ϭ * LPE; undoped GaSb grown on undoped GaSb at P ϭ 1.1 ϫ 10 16 P ϭ * 445°C (p-type ) and 400°C (n-type), Ref. 16 N ϭ 3.8 ϫ 10 15 ρ ϭ * ρ ϭ * µ ϭ * µ p ϭ 620; µ n ϭ 7,700 Molecular beam epitaxy (MBE); Undoped GaSb P ϭ 3 ϫ 10 12 P ϭ * on GaSb or on semi-insulating GaAs substrates at ρ ϭ * ρ ϭ * 600-630°C, Ref. 17 µ ϭ 500 µ ϭ * MBE; Te-doped GaSb on (311)B GaSb, Ref.…”
Section: Growth Technique and Conditions 300 K 77 Kmentioning
confidence: 99%
“…Numerous attempts have been made to reduce the native defect content by growing the crystals under varying conditions. 7,[11][12][13][14][15][16][17][18][19][20] Table I summarizes some of the key parameters that resulted in lower carrier concentration or higher resistivity in GaSb. In this paper, we report the electrical properties of tellurium (Te)-compensated, GaSb bulk crystals of 50-mm diameter (2-in.…”
Section: Introductionmentioning
confidence: 99%
“…Recently much attention has been focused on GaSb and heterostructures based on Sb narrow-gap semiconducting compounds due to their applicability in opto-electronic devices, such as lasers and photodetectors for near and mid-infrared region [1 to 3]. The growth of GaSb layers of semiconductor quality has been achieved by different techniques: liquid phase epitaxy [4], metal-organic chemical vapor deposition (MOCVD) [5], and molecular beam epitaxy [6,7]. The review of basic results and device related characteristics has been published in [1].…”
Section: Introductionmentioning
confidence: 99%